The effect of financial literacy and love of money on the financial management behavior of generation z - Ridhota Madini; M. Irfani Hendri; Helma Malini; Giriati Giriati; Ikram Yakin (International Journal of Applied Finance and Business Studies, 2023)
Present-day Generation Z encounters financial obstacles that will have long-term consequences on the collective financial welfare of future generations, and their decision-making processes transpire under more adverse conditions than those of prior generations. Nevertheless, there remains a dearth of research that thoroughly examines the financial management behavior of Generation Z, particularly regarding how financial literacy, love of money, and lifestyle impact this behavior. The financial management behavior focuses on using money effectively and efficiently. This study will investigate how financial literacy and love of money influence the financial management behavior of urban Generation Z members in Indonesia, using lifestyle as a mediator. Quantitative research is conducted and analyzed using SEM AMOS 22. The study collected data through a questionnaire from 232 respondents using a purposive sampling technique. According to the findings, financial literacy and love of money positively and significantly affect financial management behavior, mediated by lifestyle. These findings can assist related parties in devising strategic policies in micro and macroeconomics and can aid Generation Z's thought process in comprehending financial management behavior.